2010
DOI: 10.1038/ja.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Aspernidine A and B, prenylated isoindolinone alkaloids from the model fungus Aspergillus nidulans

Abstract: Filamentous fungi produce a multitude of bioactive natural products, which cover a broad range of useful pharmaceutical activities. Many of these compounds were discovered by traditional natural product screening approaches and have found various applications in modern medicine. 1,2 Through recent whole-genome sequencing projects, however, we become increasingly aware that the biosynthetic potential of microorganisms is much higher than expected. 3 In many cases, the number of putative biosynthetic genes of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…However, this concept that one strain can produce many different compounds was already introduced in 1983 by Frisvad and Filtenborg for Penicillium species, where it was shown that the species examined had specific profiles of secondary metabolites, backed up by examining a large number of isolates of each species [31]. Furthermore, they used more than one medium for production of the different secondary metabolites to get the broadest possible profile, a concept also later recommended by Bode et al [121], Bills et al [122], Scherlach et al [123], Kjer et al [124], Nielsen et al [125], Tormo et al [126], and Frisvad [127,128]. Media that has been very useful for screening filamentous fungi have included yeast extract sucrose (YES) agar, Czapek yeast autolysate (CYA) agar, malt extract agar, and oat meal agar.…”
Section: Secondary Metabolite Profiles and (One Strains Many Compoundmentioning
confidence: 97%
“…However, this concept that one strain can produce many different compounds was already introduced in 1983 by Frisvad and Filtenborg for Penicillium species, where it was shown that the species examined had specific profiles of secondary metabolites, backed up by examining a large number of isolates of each species [31]. Furthermore, they used more than one medium for production of the different secondary metabolites to get the broadest possible profile, a concept also later recommended by Bode et al [121], Bills et al [122], Scherlach et al [123], Kjer et al [124], Nielsen et al [125], Tormo et al [126], and Frisvad [127,128]. Media that has been very useful for screening filamentous fungi have included yeast extract sucrose (YES) agar, Czapek yeast autolysate (CYA) agar, malt extract agar, and oat meal agar.…”
Section: Secondary Metabolite Profiles and (One Strains Many Compoundmentioning
confidence: 97%
“…It was shown that if the producing host was grown under alternative physicochemical conditions compared with the standard laboratory growth conditions, it will possess the ability to express the originally silent gene clusters. [13][14][15] Co-cultivation of microorganisms and the application of iChip (isolation chip) have also been proved to be successful in activating the silent gene cluster.…”
Section: Drug Discovery In the Post-genomic Eramentioning
confidence: 99%
“…It was shown that if the producing host was grown under alternative physicochemical conditions compared with the standard laboratory growth conditions, it will possess the ability to express the originally silent gene clusters. [13][14][15] Co-cultivation of microorganisms and the application of iChip (isolation chip) have also been proved to be successful in activating the silent gene cluster. 16 Genomics-driven approaches 17 including mainly genome editing and genome engineering technologies by means of genetic manipulation of the target genome is believed to the most efficient but challenging and time-consuming methods to activate the silent or weakly-expressed gene clusters.…”
Section: Drug Discovery In the Post-genomic Eramentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The genus Aspergillus (Moniliaceae), with over 180 species, has attracted considerable attention as a rich source of alkaloids, terpenoids, xanthones, polyketides and etc, some of which showed antifungal, antibacterial, anti-HIV and cytotoxic activities. [3][4][5] In order to obtain new bioactive metabolites from marine fungi, we investigated on the marine fungal strain Aspergillus sydowii SCSIO 00305 isolated from a healthy tissue of Verrucella umbraculum. Bioassay-guided fractionation led to the isolation of a new indole diketopiperazine alkaloid, cyclotryprostatin E (1), together with nine known ones, [4-(2-methoxyphenyl)-1-piperazinyl][(1-methyl-1H-indol-3-yl)]-methanone (2), cyclotryprostatin B (3), 6 fumiquinazoline D (4), 7 fumitremorgin B (5), 8 fumiquinazoline C (6), 7 fumiquinazoline B (7), 7 fumiquinazoline A (8), 7 fumiquinazoline F (9), 7 fumiquinazoline G (10) 7 from a culture broth of the strain.…”
mentioning
confidence: 99%